Dependence of critical filling level on excitation amplitude in a rectangular sloshing tank. (15th May 2018) - Lu, Yucen; Zhou, Tongming; Cheng, Liang; Zhao, Wenhua; Jiang, Hongyi
Abstract: A series of experiments has been conducted to investigate the fluid sloshing at the first mode (i.e. half wavelength exists inside the tank) for different filling levels in a rectangular tank. For each filling level, fluid sloshing was driven by forced tank motions in the horizontal plane with excitation amplitudes of 0.127 cm, 0.254 cm, 0.508 cm and 0.635 cm, respectively. Pressure variations on the side wall of the tank and wave elevation inside the tank were measured simultaneously using four pressure sensors and a wave gauge. It was found that the filling level at which the maximum sloshing amplitude occurs, namely the critical filling level, decreases as the excitation amplitude increases. A theoretical analysis was conducted to provide a physical explanation for this trend. It was also found that an increase in the damping of the system leads to a shift of the critical filling level to a higher value. The pressure on the tank sidewall is found to correlate well with the response amplitude of the water level in the tank since small excitation amplitudes were used in this study. Highlights: The maximum sloshing amplitude occurs at the critical filling level. Critical filling level decreases with the increase in the excitation amplitude. The increase in the damping of the system leads to a shift of the critical filling level to a higher value.